Orang Ulu of Borneo photographs from the archives of Sarawak Museum - Horn, Christine (Opus Publications, 2012)
This book presents photographs taken in the Orang Ulu longhouses and villages of the Baram and Tinjar rivers in Sarawak. The images show the arts and crafts, religious ceremonies, longhouses and their environments and other subjects that are unique to these places and communities. The images are part of the large, and for the most part undocumented, collection of photographs from the archive of the Sarawak Museum in Kuching. These pictures were chosen from a stock of around 1500 black and white medium format photographs taken in and around the longhouses and villages of the people called Orang Ulu, and many of them have never been published before. The photographs illustrate aspects of the way of life and the traditional culture and customs of the Orang Ulu from the 1950s onwards. They are family photographs, historical records, ethnographic documents of local culture and traditions.